3rd International Conference on Radiation Safety & Security in Healthcare Services Proceedings of the Thirs, ICRSSHS, Dewan Budaya USM, Penang, Malaysia - Zainon, R.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book presents the proceedings of the 3rd International Conference on Radiation Safety & Security in Healthcare Services. The conference was held at Universiti Sains Malaysia in Penang on 19th-20th August 2017.
Keywords: Biomedical engineering; Medical physics; Radiology; Practice of medicine; Hospitals -- Administration; Biomedical Engineering and Bioengineering; Medical Physics; Radiology; Practice and Hospital Management